Development and Validation of Work/Family Conflict Scale for Women - Ayesha Sarfaraz, PhD; Ayesha Khalid, PhD (Corresponding author); Shirmeen Ijaz, PhD; Shehla A. Yasin, PhD; Qurat-ul-Ain; Ruhi Khalid, PhD (Al-Qanṭara, 2023)
: The present study was carried out to develop and validate an indigenous tool for assessing work/family conflict of working women. The study was carried out in three phases. In phase I, semi-structured interviews were conducted with 38 working women both married and unmarried belonging to diverse professions. Initial item pool of 74 items was generated from qualitative data; review of literature and from existing measures of work/family conflict. After an extensive scrutiny and evaluation by a panel of 5 judges, 62 items were selected or the final scale using a five-point rating format. In phase II, dimensionality and reliability of the scale were established. It was then administered to a sample of 463 participants (married =228, unmarried =235) with the age ranged from 24 to 53 years (M = 30.49, SD = 4.17). exploratory factor analysis using principal component analysis was carried out to determine the dimensionality of the scale, based on the result of factor analysis certain items were removed resulting in a 57 item measure of work/family conflict having two subscales (work to family conflict and family to work conflict) each measuring three aspects of the conflict time-based, strain-based and behavior-based. In Phase III, validity of scale was established, the results showed that the scale has convergent validity with negative spillover scale (r =.56, p < .001) and discriminant validity with positive spillover scale (r = -.18, p < .01).